Development of methane decarbonisation based on liquid metal technology for CO2-free production of hydrogen. (25th May 2016) - Abánades, Alberto; Rathnam, Renu Kumar; Geißler, Tobias; Heinzel, Annette; Mehravaran, Kian; Müller, George; Plevan, Michael; Rubbia, Carlo; Salmieri, Delia; Stoppel, Leonid; Stückrad, Stefan; Weisenburger, Alfons; et al.
Abstract: The development of a low-carbon technique to produce hydrogen from fossils would be of great importance during the transition to a long-term sustainable energy system. Methane decarbonisation, the well-known transformation of methane into hydrogen and solid carbon, is a potential candidate in this regard. At the Institute for Advanced Sustainability Studies (IASS), a new alternative technology for methane decarbonisation applying liquid metal technology was proposed and an ambitious programme was set up in collaboration with the Karlsruhe Institute of Technology (KIT). The comprehensive programme included the following: conceptual design of a liquid metal bubble column reactor and material testing, process engineering incorporating carbon separation and hydrogen purification, and a socio-economic analysis. In the present paper, an overview of the programme along with some of the results, are presented. Results from the experimental campaigns show that the liquid metal reactor design works effectively in producing hydrogen and carbon separation. Other aspects of the technology such as socio-economics, environmental impact, and scalability also seem to be favourable making methane decarbonisation based on liquid metal technology a potential candidate for CO2 -free hydrogen production. Highlights: A comprehensive programme to fast track the deployment of methane decarbonisation on an industrial scale. Development of a novel liquid metal reactor concept for CO2 -free hydrogen production. Process engineering, socio-economic and environmental aspects are also covered. Successful laboratory scale demonstration of the technical viability of the proposed process.